ENGLISH FOUR AND FIVE WORD ANATOMICAL TERMS AND THEIR LATIN EQUIVALENTS IN THE TEXTBOOK HUMAN ANATOMY(VOL.I) - Litevkienė, Nijolė (PROFESSIONAL STUDIES: Theory And Practice, 2023)
This research is aimed to identify the peculiarities of compound English and Latin anatomical terms, based on comparative description of structural forms of compound terms. An essential role in medical vocabulary creation has been played by Greek, Latin, English. This research was based on the use of such methods of linguistic analysis. In the textbook „Human Anatomy‟, M. Prives, V. Bushkovich, N. Lisenkov offer a progressive view descriptive, evolutionary, functional, and practical anatomy. Medical terms in the texbook can be basically divided into one-word and multiple word terms. One-word terms can be simple words, derived words, compounds, or combination of derived and compound words. Coumpoud anatomical terms can consist of two-five words. The article presents the analysis of four-word and five-word English and Latin anatomical terms and the analysis of their specific configurations.